Powdery mildew resistance of barley accessions from Dagestan - R. A. Abdullaev; T. V. Lebedeva; N. V. Alpatieva; B. A. Batasheva; I. N. Anisimova; E. E. Radchenko (Вавиловский журнал генетики и селекции)
Powdery mildew caused by the parasitic fungus Blumeria graminis (DC.) Golovin ex Speer f. sp. hordei Marchal is one of the most common diseases of barley. Growing resistant varieties can significantly minimize harmful effects of the pathogen. The specificity in the interaction between the fungus and its host plant requires a continuous search for new donors of the resistance trait. The powdery mildew resistance of 264 barley accessions from Dagestan and genetic control of the trait in resistant forms were studied under field and laboratory conditions. Forty-seven barley lines carrying previously identified powdery mildew resistance genes were also examined. During three years, the experimental material was evaluated under severe infection pressure at the Dagestan Experiment Station of VIR (North Caucasus, Derbent). Juvenile resistance against the Northwest (St. Petersburg, Pushkin) pathogen population was evaluated in a climatic chamber. The genetic control of B. graminis resistance in the selected accessions was studied with the application of hybridological and molecular analyses. The level of genetic diversity of Dagestan barley for effective resistance to powdery mildew is very low. Only two accessions, VIR-23787 and VIR-28212, are resistant against B. graminis at both seedling and adult plant stages. The high-level resistance of breeding line VIR-28212 originating from barley landrace VIR-17554 (Ep-80 Abyssinien) from Ethiopia is controlled by the recessive gene mlo11. Accession VIR-17554 is heterogeneous for the studied trait, with the powdery mildew resistant genotypes belonging to two varieties, dupliatrum (an awnless phenotype) and nigrinudum (an awned phenotype). In accession VIR-23787, a recessive resistance gene distinct from the mlo11 allele was identified. This accession is supposed to be protected by a new, effective pathogen resistance gene.